Effectiveness of a Spectacle Lens with a Specific Asymmetric Myopic Peripheral Defocus: 12-Month Results in a Spanish Population - Miguel Ángel Sánchez-Tena; Jose Miguel Cleva; Cesar Villa-Collar; Marta Álvarez; Alicia Ruiz-Pomeda; Clara Martinez-Perez; Cristina Andreu-Vazquez; Eva Chamorro; Cristina Alvarez-Peregrina (MDPI AG, 2024)
Background: Different designs of ophthalmic lenses have been studied to control the progression of myopia in children. This study aims to evaluate the short-term efficacy of a new design of ophthalmic lens with asymmetric myopic peripheral defocus (MPDL) on myopia progression in children compared to a control group wearing a single-vision lens (SVL). Methods: Children aged 5 to 12 with myopia up to −0.50 D, astigmatism and anisometropia under 1.50 D, and corrected visual acuity over 20/20 were randomized to either the study group (MPDL) or control group (SVL). The myopia progression was evaluated by measuring axial length (AL) growth (IOL Master; Zeiss) over a period of one year. Results: Ninety-two subjects were recruited. Forty-six children were randomly assigned to the control group, and 46 to the study group. In total, 83 children completed the clinical trial, with a mean age of 10.81 [9.53-11.92] years, among which 59.04% were female. After one year of treatment, there was less AL elongation in the study group compared to the control group (0.16 ± 0.16 mm vs. 0.24 ± 0.16 mm, p = 0.034). Conclusions: The MPDL significantly reduced the absolute growth of AL by 39% (p = 0.014) and relative growth of AL by 37.3% (p = 0.012) after 12 months in comparison to the control group in a Spanish population.